Method of local linear approximation for nonlinear discrete equations - Slyusarchuk, V. Yu. (Ukrains’kyi Matematychnyi Zhurnal, 2019)
UDC 517.988.6 We obtain new conditions for the existence of bounded solutions of nonlinear discrete equations with application of the local linear approximation of these equations.